2014
DOI: 10.1002/gps.4180
|View full text |Cite
|
Sign up to set email alerts
|

Integration of geriatric mental health screening into a primary care practice: a patient satisfaction survey

Abstract: Objective Colocation of mental health screening, assessment, and treatment in primary care reduces stigma, improves access, and increases coordination of care between mental health and primary care providers. However, little information exists regarding older adults’ attitudes about screening for mental health problems in primary care. The objective of this study was to evaluate older primary care patients’ acceptance of and satisfaction with screening for depression and anxiety. Methods The study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…We had earlier found that the experience of being screened was itself well-accepted by the patients [24, 25]. Further, we were able, without employing research assistants dedicated to the project and therefore avoiding additional expenditure, to screen over one-third of the unique individuals presenting to the center during the study period.…”
Section: Discussionmentioning
confidence: 94%
“…We had earlier found that the experience of being screened was itself well-accepted by the patients [24, 25]. Further, we were able, without employing research assistants dedicated to the project and therefore avoiding additional expenditure, to screen over one-third of the unique individuals presenting to the center during the study period.…”
Section: Discussionmentioning
confidence: 94%
“…Early detection will help identify psychological or mental health problems in the elderly. 20 This study has some limitations. The CGA should be carried out for a new elderly patient.…”
Section: Discussionmentioning
confidence: 91%
“…Since the time of this study, integration of mental health in PC has become more possible with incentives from the American Recovery and Reinvestment Act of and the Patient Protection and Affordable Care Act, of . Even in this integrated care setting, Samuels et al () learned similarly that half found frequent screenings acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…To date, we found only two other relevant studies evaluating OAs' willingness to engage in depression screening (Davis et al, ; Samuels et al, ), both finding that most were willing to engage in depression screening. Even fewer studies have evaluated brief educational interventions for depression to reduce patient resistance.…”
Section: Introductionmentioning
confidence: 99%